HYBRID LEARNING BERBASIS DIGITAL SEBAGAI STRATEGI RESILIENSI PEMBELAJARAN PASCABENCANA - Parihin Parihin; Joko Suseno; Velya Pramesthi Putri Ragil; Ahmad Subagyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The tornado disaster that damaged learning facilities at SMAN 2 Gunungputri required the school to develop an adaptive strategy to ensure the continuity of educational services. This study aimed to describe the implementation of Hybrid Learning supported by digital technology as a strategy for strengthening learning resilience in a post-disaster context. The study employed a qualitative approach using a single-case study design involving the principal, vice principal for curriculum affairs, teachers, students, and parents as research participants. Data were collected through semi-structured interviews, non-participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that the implementation of Hybrid Learning successfully sustained learning continuity by strengthening four dimensions of learning resilience, namely institutional, teacher, student, and social resilience. This adaptive strategy restored the effectiveness of instructional activities, enhanced the digital competencies and digital literacy of both teachers and students, and reinforced collaboration between schools and parents in supporting the learning process. Although challenges related to internet connectivity, learning devices, and monitoring of online learning remained, the school was able to adapt effectively to maintain the quality of educational services. The study concludes that digitally supported Hybrid Learning is not merely an alternative instructional approach during emergencies but also a learning resilience strategy that enhances schools' adaptive capacity in responding to disasters while promoting sustainable digital transformation in education. ABSTRAK Bencana angin puting beliung yang merusak fasilitas belajar di SMAN 2 Gunungputri menuntut sekolah mengembangkan strategi adaptif untuk menjaga keberlangsungan proses pendidikan. Penelitian ini bertujuan mendeskripsikan implementasi Hybrid Learning berbasis digital sebagai strategi membangun resiliensi pembelajaran pada kondisi pascabencana. Penelitian menggunakan pendekatan kualitatif dengan desain single case study yang melibatkan kepala sekolah, wakil kepala sekolah bidang kurikulum, guru, peserta didik, dan orang tua sebagai informan. Data dikumpulkan melalui wawancara semi-structured, observasi nonpartisipan, dan studi dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa penerapan Hybrid Learning mampu mempertahankan keberlangsungan pembelajaran melalui penguatan empat dimensi resiliensi, yaitu resiliensi institusional, guru, peserta didik, dan sosial. Adaptasi tersebut ditunjukkan oleh pemulihan efektivitas pembelajaran, meningkatnya kompetensi dan literasi digital guru serta peserta didik, dan menguatnya kolaborasi antara sekolah dengan orang tua dalam mendukung pembelajaran. Meskipun masih dihadapkan pada keterbatasan jaringan internet, perangkat belajar, dan pengawasan pembelajaran daring, sekolah mampu melakukan penyesuaian yang menjaga kualitas layanan pendidikan. Penelitian ini menyimpulkan bahwa Hybrid Learning berbasis digital tidak hanya menjadi alternatif pembelajaran pada situasi darurat, tetapi juga merupakan strategi resiliensi pendidikan yang memperkuat kapasitas adaptasi sekolah dalam menghadapi bencana sekaligus mendukung transformasi pendidikan yang berkelanjutan.